2015
DOI: 10.1016/j.celrep.2015.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Origin of a Non-Clarke’s Column Division of the Dorsal Spinocerebellar Tract and the Role of Caudal Proprioceptive Neurons in Motor Function

Abstract: Summary Proprioception, the sense of limb and body position, is essential for generating proper movement. Unconscious proprioceptive information travels through cerebellar-projecting neurons in the spinal cord and medulla. The progenitor domain defined by the basic helix-loop-helix (bHLH) transcription factor, ATOH1, has been implicated in forming these cerebellar-projecting neurons; however, their precise contribution to proprioceptive tracts and motor behavior is unknown. Significantly, we demonstrate that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(114 citation statements)
references
References 61 publications
(103 reference statements)
13
89
0
Order By: Relevance
“…SCTs consist of an ipsilateral-projecting population (the dorsal SCT, DSCT) and a contralateral-projecting population (the ventral SCT, VSCT). Studies have shown that dI1i and dI1c neurons contribute to both the DSCT and VSCT, respectively (Bermingham et al, 2001;Miesegaes et al, 2009;Wilson et al, 2008;Yuengert et al, 2015). However, recent work using Atoh1 lineage tracing shows that the dI1 population only makes a subset of the DSCT and VSCT, suggesting that there are other developmental sources for these tracts (Yuengert et al, 2015).…”
Section: Proprioceptionmentioning
confidence: 95%
See 4 more Smart Citations
“…SCTs consist of an ipsilateral-projecting population (the dorsal SCT, DSCT) and a contralateral-projecting population (the ventral SCT, VSCT). Studies have shown that dI1i and dI1c neurons contribute to both the DSCT and VSCT, respectively (Bermingham et al, 2001;Miesegaes et al, 2009;Wilson et al, 2008;Yuengert et al, 2015). However, recent work using Atoh1 lineage tracing shows that the dI1 population only makes a subset of the DSCT and VSCT, suggesting that there are other developmental sources for these tracts (Yuengert et al, 2015).…”
Section: Proprioceptionmentioning
confidence: 95%
“…5). Indeed, Atoh1 lineage neurons (dI1), which are born from the dorsal-most progenitor domain, migrate ventrally to the intermediate gray area of the spinal cord (laminae V-VII) with a smattering of neurons even reaching the ventral horn (Miesegaes et al, 2009;Wilson et al, 2008;Yuengert et al, 2015). In addition, dI2 and dI3 neurons settle in the intermediate to ventral parts of the spinal cord (Bui et al, 2013;Hadas et al, 2014;Quinones et al, 2010).…”
Section: The Migration Of Neurons During Spinal Cord Circuit Formationmentioning
confidence: 99%
See 3 more Smart Citations